Parameterization of interatomic potential by genetic algorithms: A case study - Ghosh P.S.; Ranawat Y.S.; Arya A.; Dey G.K. (My University, 2025)
A framework for Genetic Algorithm based methodology is developed to systematically obtain and optimize parameters for interatomic force field functions for MD simulations by fitting to a reference data base. This methodology is applied to the fitting of ThO 2 (CaF 2 prototype) - a representative of ceramic based potential fuel for nuclear applications. The resulting GA optimized parameterization of ThO 2 is able to capture basic structural, mechanical, thermo-physical properties and also describes defect structures within the permissible range. © 2015 AIP Publishing LLC.